Pengungkapan Risiko Keamanan Siber: Dampaknya Terhadap Hubungan Pelanggan-Pemasok Dalam Rantai Pasok Perusahaan - Mohamad Chaidir; Ngadi Permana; Grace Yulianti (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2024)
This study explores the impact of cybersecurity risk disclosure on customer-supplier relationships in corporate supply chains through a qualitative literature review approach. The findings reveal that transparency in cybersecurity risk disclosure enhances trust, relationship stability, and operational efficiency within supply chains. Conversely, a lack of disclosure or poor risk management can damage reputations, create uncertainty, and weaken collaboration between business partners. The study also highlights the importance of adequate regulations, risk mitigation strategies, and the adoption of new technologies in managing cybersecurity. While offering significant insights, this study has limitations, including reliance on secondary literature and variations in industry contexts. Future research is recommended to include empirical testing and the exploration of new technologies to strengthen cybersecurity risk management in supply chains.